Evaluation of the Utility of a Transition Workbook in Preparing Adolescent and Young Adult Cancer Survivors for Transition to Adult Services: A Pilot Study. (March 2016) - Bashore, Lisa; Bender, Joyce
Transition to adult care for adolescent and young adult survivors is challenging and is inclusive of several factors like knowledge and developmental, emotional, and social status of survivors and parents. This pilot study addressed the feasibility of a transition workbook, a method of preparing adolescent and young adults to transition to adult care. Using a mixed methods design, investigators also measured transition worry and readiness in 30 survivors. Support was provided throughout a 6-month period as survivors and parents completed the workbook. The workbook included sections about the treatment history of survivors, when and who to call for worrisome symptoms, prescriptions and insurance, educational goals for health practices and how to get there, and independent living. Twenty survivors completed the study and reported greater worry about leaving pediatric oncology but indicated the need to make changes to transition to adult care. Ambiguity and intimidation about transitioning to adult providers and comfort in pediatric setting were themes expressed by survivors. Results indicate the need for adult/pediatric collaborative transition programs using various standardized methods of addressing transition readiness and evaluation.